Customizable VR design of friends interaction for social story - Tee , Zi Jun (2024)

(untitled)
The primary goal of this project is to construct an immersive and customizable virtual reality (VR) experience to empower autistic primary school students to rehearse social interactions involved in forming new friendships, within a simulated classroom environment. The customized VR setting provides opportunities for autistic students to safely hone their social interactions including self-introductions, initiating dialogues, deciphering social cues, and building friendship. Parents can tailor class background, classroom objects, language, sound setting, and scenarios to match with their child's actual classroom contexts and preferences. By harnessing VR's interactive features, this project seeks to refine targeted interpersonal skills and elevate social communication adeptness in autistic students. Expert psychologists will assess the solution's viability, usability, engagement, and learning potential. Their evaluations will provide insights into effectively using VR technology to enhance the social skillset of autistic students. This project constitutes a component of a larger VR project with a team of three working together in software development, software testing, and VR content creation. Each member is tasked to construct one scenario that could occur during school. This project scope is to assist autistic primary school students in forming friendships through this customizable VR application.